2022
DOI: 10.1111/vec.13235
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of amanitin exposure (amatoxicosis) in a dog with a point‐of‐care diagnostic test

Abstract: Objective: To describe the rapid diagnosis, treatment, and clinical course of a dog that ingested an amanitin-containing mushroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…5 Amatoxins effectively inhibit eukaryotic RNA polymerase II, hindering mRNA transcription and protein synthesis and ultimately leading to cellular necrosis. A single toxic mushroom may contain over 20 mg of amatoxins, 6 and the average concentration of α-amanitin in mushrooms ranges from approximately 0.5 to 2 mg/g. 7 The estimated oral median lethal dose (LD50) for α-amanitin is 0.1 mg/kg in humans.…”
Section: ■ Introductionmentioning
confidence: 99%
“…5 Amatoxins effectively inhibit eukaryotic RNA polymerase II, hindering mRNA transcription and protein synthesis and ultimately leading to cellular necrosis. A single toxic mushroom may contain over 20 mg of amatoxins, 6 and the average concentration of α-amanitin in mushrooms ranges from approximately 0.5 to 2 mg/g. 7 The estimated oral median lethal dose (LD50) for α-amanitin is 0.1 mg/kg in humans.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In one retrospective study, 13/59 dogs (26%) with confirmed alpha-amanitin exposure survived discharge, and none of these patients were documented to have developed adrenal insufficiency after intoxication at follow-up appointments [ 3 ]. Smaller studies have documented longer follow-up periods without evidence of adrenal disease [ 8 , 9 ]. A clearer understanding of post-intoxication outcomes would help veterinarians prepare pet owners to understand the implications and long-term consequences of amanitin intoxication.…”
Section: Introductionmentioning
confidence: 99%